An analysis of cheap clothing imports as a challenge affecting the revival of textile and clothing manufacturing sector: A case study of Zimbabwe (2000-2014) - Majoni, Learnmore (2017)
Zimbabwe’s clothing and textile sector has been facing a serious challenge from cheap imported clothing as well as second–hand used clothing and there has been no serious concern about this problem from policy makers. The research is titled an analysis of cheap clothing imports as a challenge affecting the revival of the textile and clothing sector. In this regard the research appraised the negative impact that cheap imported clothing and textiles is posing to the local textile and clothing producers. Revival and retooling of clothing and textile sector has been a serious issue of concern in Zimbabwe however, it is failing to materialise. In essence the primary objective of this research is to understand how cheap imports have hindered the revival of Zimbabwe textile and clothing sector, as well as apprehending the factors that has contributed to its downfall, based on the perceptions of stakeholders and representative. Instead of recovering the clothing and textile sector continue to downsize and shrink, therefore, economic benefits such as national employment, value addition, foreign exchange earnings and Gross Domestic Product remain a white elephant to the economy of Zimbabwe. The methodology of the research is largely qualitative and quantitative as the problem understudy requires in depth information on both statistics of the sector, the effect and impact of cheap clothing imports towards the revival of clothing and textile sector in Zimbabwe. The research has been built upon endogenous theory which denotes the modelled simultaneous relationship between imports and protection, high levels of imports intensifies protection. The research concluded that cheap imported clothing imports is the major problem towards revival of clothing and textile sector, as it imposes unfair market competition. However, some factors such as debt, inconsistent government policies and unavailability of working capital also affects the revival of the sector. The research recommended that there should a total ban on trade of imported clothing as well as second-hand clothing; the government should tighten its borders to ensure that there is no smuggling of such products.